2023
DOI: 10.1371/journal.pone.0278078
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and information sources towards Helicobacter pylori in Jordan

Abstract: In 2017, the Jordanian Ministry of Health reported that gastric cancer was one of Jordan’s most diagnosed cancers. Gastric cancer is often linked to Helicobacter pylori, one of the foremost risk factors. Despite the high prevalence of H. pylori in Jordan, no information is available regarding the general population’s awareness of the harmful effects of this pathogen. The study aims to assess the knowledge and the impact of the source of knowledge on H. pylori among the general population in Jordan. A cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The researchers emphasized that social programmes and campaigns should be organized to increase awareness. The researchers specifically stated that society should be encouraged to obtain information about H pylori from “reliable sources.” [ 26 ] In another study conducted with 500 participants in the United Arab Emirates, it was emphasized that the general knowledge of the participants about H pylori was weak. In this study, it was reported that only 24.6% of the participants had heard of H pylori , and it was emphasized that 61% of the participants did not know the link between H pylori and stomach cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers emphasized that social programmes and campaigns should be organized to increase awareness. The researchers specifically stated that society should be encouraged to obtain information about H pylori from “reliable sources.” [ 26 ] In another study conducted with 500 participants in the United Arab Emirates, it was emphasized that the general knowledge of the participants about H pylori was weak. In this study, it was reported that only 24.6% of the participants had heard of H pylori , and it was emphasized that 61% of the participants did not know the link between H pylori and stomach cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been hypothesized that males and females have different plasma [K + ] set points than males for handling high K + loads [28]. Indeed, this whole-body K + model may be extended to consider sex differences as well as unique physiological states in females that undergo major changes in K + regulation such as pregnancy and lactation [37, 40, 45].…”
Section: Discussionmentioning
confidence: 99%
“…The general community appears to lack adequate knowledge regarding H. pylori, particularly regarding its mode of transmission (Hafiz et al, 2021). However, a study conducted by Alaridah et al (2023) revealed the presence of misconceptions and highlighted the need for further expansion and support in knowledge dissemination concerning H. pylori.…”
Section: Risk Factorsmentioning
confidence: 99%